Peran Guru Pesantren Dalam Menumbuhkan Motivasi Belajar Pai Dan Prestasi Akademik Siswa Di Smk Subulul Huda Kembangsawit - Muhammad Imron (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
The integration of pesantren (Islamic boarding school) education with vocational high schools (SMK) offers a unique educational model, which aims to produce not only skilled graduates but also those with Islamic character. In this model, the role of the pesantren teachers is key in shaping student motivation and achievement. This research aims to analyze the role of pesantren teachers in fostering learning motivation in Islamic Religious Education (PAI) and student academic achievement, as well as identifying the supporting and inhibiting factors at SMK Subulul Huda Kembangsawit. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, participatory observation, and documentation studies involving pesantren teachers, dormitory caregivers, the school principal, and students. The research findings indicate that pesantren teachers play the roles of: 1) Parents and guides who create emotional connections; 2) Role models of morality and spirituality; 3) Motivators who ignite learning enthusiasm; and 4) Facilitators who integrate Islamic values. The main inhibiting factors include a dual curriculum burden, ineffective time management, limited facilities, and a lack of synergy between the school and the pesantren. Pesantren teachers play a central and multifunctional role in the integrative educational ecosystem. The success of this model heavily depends on the teachers' exemplary conduct, personal approach, and ability to create a religious and conducive learning environment.